Exfoliative erythroderma as a paraneoplastic presentation of adenocarcinoma of the gallbladder - Eltawansy, Sherif Ali; Agrawal, Abhinav; Modi, Anar; Hassanien, Samaa; Zhang, Bin; Pei, Zhengtong; Ghali, Wael (Journal of Gastrointestinal Oncology; Vol 6, No 2 (April 13, 2015): Journal of Gastrointestinal Oncology, 2014)
We report a case of a 71-year-old Caucasian male presenting with an exfoliative skin rash all over his body. The patient was also found to have a huge gall bladder mass extending into the liver that turned out to be adenocarcinoma of the gall bladder on biopsy. Gall bladder cancer usually presents with abdominal pain, swelling or jaundice. We report only the second case in literature of a gall bladder adenocarcinoma presenting with exfoliative erythroderma as its paraneoplastic presentation.